Dual Molecular Loading: Spatially Controlled Molecular Encapsulation in Natural Pine Pollen Microcapsules (Part. Part. Syst. Charact. 9/2018). (12th September 2018) - Prabhakar, Arun Kumar; Potroz, Michael G.; Park, Soohyun; Miyako, Eijiro; Cho, Nam‐Joon
Abstract : The cover represents the dual molecular encapsulation using natural pine pollen, as described in article number1800151 by Eijiro Miyako, Nam‐Joon Cho and coworkers. By simple vacuum and passive loading methods, they demonstrate that diverse molecules are binary encapsulated into the pollen microcapsule. In addition, the loaded molecules can be effectively released from the pollen. Furthermore, the unique shell structure of the pollen capsule helps to conserve the structure of protein molecules.